Respiratory insufficiency in patients after neurosurgical procedures performed in the sitting position - Wojtan, Stanisław; Kózka, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Neurosurgical procedures in the area of the posterior cranial cavity and cervical spine may be performed in the prone, lateral and sitting position. However, sitting position may lead to numerous intraoperative complications and result with patient’s respiratory insufficiency after the surgery. Aim. The aim of this paper was to evaluate the impact of patient’s clinical status before the surgery, anaesthetics used during the procedure, surgery duration and intraoperative complications, which occurred during this intervention, on the incidence of respiratory insufficiency in patients after neurosurgical procedures performed in the sitting position. Material and methods. The analysis included 139 neurosurgical procedures performed in the sitting position. 60% of the study group were females and remaining 40% were men. The most frequent cause of the surgery included: cerebellum tumours (47%) and cerebello-pontine angle tumours (29%). Arterial blood pressure variations, heart arrhythmia, and air embolism were the main intraoperative complications. Results and conclusions. Respiratory insufficiency was diagnosed after surgery in 32% of patients. It concerned mainly the oldest patients, with the surgical risk ratio ASA between 3 and 4, those who were reoperated or whose surgery lasted longer than four hours. Almost half of the group with respiratory insufficiency suffered from three or more intraoperative complications at the same time. Also, every second patient with one of the complications i.e. tachycardia, the increase of arterial blood pressure or air embolism, had respiratory insufficiency after the neurosurgical procedure. All patients who were operated because of aneurysms or angiomas of the posterior fossa were free from respiratory insufficiency.